Effect of orally administered sodium bicarbonate on caecal pH - Taylor, Elizabeth Ardelle (Kansas State University, 2014)
Reasons for performing study: Caecal acidosis is a central event in the metabolic cascade that occurs following grain overload. Buffering the caecal acidosis by enterally administered sodium bicarbonate may be beneficial to affected horses. Objectives: To determine the effect and duration of enterally administered sodium bicarbonate (NaHCO[subscript]3) on caecal pH in healthy horses. Study design: Prospective controlled study using normal horses with caecal cannulas Methods: 9 horses previously fitted with a caecal cannula. 6 horses received 1.0 g/kg bwt NaHCO[subscript]3 via nasogastric tube and 3 control horses were given 3 L of water via nasogastric tube. Clinical parameters, water consumption, venous blood gases, caecal pH, faecal pH and faecal water content were measured at 6 hour intervals over a 36 hour study period. Results: Horses that received enterally administered NaHCO[subscript]3 had a significantly increased caecal pH that lasted the duration of the study. Treated horses increased their water intake, developed metabolic alcalemia, significantly increased sodium concentrations and significantly decreased potassium concentrations. Conclusions and potential relevance: Enterally administered NaHCO[subscript]3 may be beneficial in buffering the caecal acidosis that occurs following an acute carbohydrate overload
Keywords: Horse; Cecal; pH; Sodium bicarbonate; Laminitis; Veterinary Medicine (0778)